Aspek perancangan bandar yang mempengaruhi rebranding Bandaraya Alor Setar dalam konteks pelancongan - Mohd Yusri, Md Daud (2014)
The state government and the local authority are the main players in determining the image and the identity of a city. Role played by the administrator at the state and local government level are to make sure that all the planning development of a city are implemented systematically and perfectly to fulfil the purposes and the objectives fixed in the State Structural Plan and the Local Plan. The State Government and the Local Authority always need to be cautious with the public demand especially the city dwellers lived in the service areas because they have to pay for all the services supplied. Complains and uneasiness that exist among the public will indirectly tarnish both level of governments’ reputations. The continuous social well-being development through the implementation of sustainable city concept and the quality of life improvement process has to be well planned and implemented. Through the physical planning, city design, business, landscape, tourism, transportation and traffic aspects can help Kedah State and Alor Setar City Council to rebrand Alor Setar City especially the city centre area. Through the systematic land use planning will make Alor Setar more dynamic and attractive as a tourism attraction city in line with the rebranding planning.